Tingkat Kepercayaan Masyarakat Terhadap Hasil Pengukuran Volume Penyerahan Pada Pom Mini (Studi Kasus Pengendara Roda Dua Di Wilayah Bandung Raya) - Sri Marliani, Reni (Cendekia Niaga, 2021)
High demand for fuel in the community led to the emergence of fuel mini station. This increase is not always accompanied by the availability of official fuel stations. Mini fuel station existence is not only related to the law regulating the distribution of fuel in the community, but also a concern for legal metrology unit in terms of consumer protection. This study aims to measure public trust in the measurement results of mini fuel station and is carried out using descriptive methods with distributing questionnaires and interviews as data collection techniques. There were 121 respondents spread across four areas around Bandung Raya. Out of the 121 respondents, 47% stated that they frequently go to Mini fuel station for 2-3 times a week, however after further investigation, it turns out that 59% of respondents still utilize official fuel stations as their main destination for purchasing fuel. The biggest factor that causes this phenomenon is the respondents' distrust of the measurement results at Mini Fuel Station, 67% of the respondents said they were not confident about the measurement results.